Natural infection by Trypanosoma cruzi in Rhodnius robustus I infesting Attalea butyracea palms in El Zulia, Norte de Santander, Colombia - Prieto Silva, Tania; Blanco, Ingrid Yolanda; Oviedo Niño, Carolina; Gutiérrez Marín, Reinaldo (Innovaciencia, 2026)
Introduction. Palms such as Attalea butyracea function as key sylvatic ecotopes for species of the genus Rhodnius, providing shelter, suitable microclimatic conditions, and access to vertebrate hosts, thus contributing to the maintenance of Trypanosoma cruzi transmission cycles in disturbed landscapes. Objective. To evaluate the infestation of Attalea butyracea palms by triatomines and to determine natural infection by T. cruzi using parasitological and molecular methods in El Zulia, Norte de Santander, Colombia. Materials and methods. Between August and September 2021, 100 palms were sampled using modified Angulo traps. The collected insects were identified morphologically and through sequencing of the mitochondrial cytochrome b gene. Infection was assessed by microscopic examination of intestinal contents and PCR detection of T. cruzi DNA. Results. A total of 64 specimens of the genus Rhodnius were collected, with an infestation index of 30% of the sampled palms. Natural infection was 31% by microscopy and 40% by PCR. Molecular analysis confirmed the presence of Rhodnius robustus I. Conclusions. The detection of R. robustus I highlights the importance of integrating molecular surveillance to improve the accuracy of vector identification and to monitor their dispersal and adaptation capacity. Continuous entomological surveillance in natural ecotopes is essential to prevent reinfestation and to consolidate the achievements of control programs.
Keywords: : Rhodnius; Chagas disease; Trypanosoma cruzi; cytochrome b; Attalea butyracea; Colombia; Palms